2022
DOI: 10.3390/hydrology9060096
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Hydrological Functioning of Three Large Karst Springs in the Salem Plateau, Missouri, USA

Abstract: Spring discharge hydrographs can provide information on karst aquifer connectivity and responses to precipitation. However, few studies have conducted time-series analyses of spring hydrographs over multi-decadal time scales. We examine daily discharge for three large karst springs and daily precipitation for adjoining weather stations during 1928–2019 in the Salem Plateau of southern Missouri, one of the major karst regions in the USA. For different time periods, we conducted baseflow index calculations and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The geological structure of the 53 catchments considered here is characterized by a wide range of karst content [34]. It is known that karst potentially reduces or amplifies flood peaks and influences the catchment boundary due to the complex conditions for surface and groundwater flow [63,64]. A karst share influence on MAF prediction is implicitly shown in Figure 9, where it may be observed that MAF in catchments with high karst share (>50%) is generally underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The geological structure of the 53 catchments considered here is characterized by a wide range of karst content [34]. It is known that karst potentially reduces or amplifies flood peaks and influences the catchment boundary due to the complex conditions for surface and groundwater flow [63,64]. A karst share influence on MAF prediction is implicitly shown in Figure 9, where it may be observed that MAF in catchments with high karst share (>50%) is generally underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Recession methods, which involve analysis of hydrographs, can provide information about the distribution of recharge (temporal and spatial) and storage properties of the surrounding aquifer [24][25][26][27][28]. Recession analysis has primarily been applied to surface water systems [29][30][31] but it also has been utilized for karst springs to examine temporal distribution of recharge, including both diffuse and rapid components [9,20,24,[32][33][34][35]. More recently, recession analysis has been conducted on cave drips to derive storage parameters for a karst aquifer [5], showing that recession methods can be useful tools for extracting a variety of hydrologic characteristics in karst systems.…”
Section: Introductionmentioning
confidence: 99%